Novel in vitro assays to detect circulating permeability factor(s) in idiopathic focal segmental glomerulosclerosis. Issue 2 (6th November 2020) - den Braanker, Dirk J W; Maas, Rutger J; Deegens, Jeroen K; Yanginlar, Cansu; Wetzels, Jack F M; van der Vlag, Johan; Nijenhuis, Tom
Abstract: Background: Many patients with idiopathic focal segmental glomerulosclerosis (FSGS) develop recurrence of proteinuria after kidney transplantation (TX). Although several circulating permeability factors (CPFs) responsible for recurrence have been suggested, there is no consensus. To facilitate CPF identification and predict recurrence after TX, there is a need for robust methods that demonstrate the presence of CPFs. Methods: Cultured human podocytes (hPods) and human and mouse glomerular endothelial cells (ciGEnC, mGEnC) were exposed to plasmas of FSGS patients with presumed CPFs, and of (disease) controls. A visual scoring assay and flow cytometry analysis of side scatter were used to measured changes in cellular granularity after exposure to plasma. Results: Nine out of 13 active disease plasmas of 10 FSGS patients with presumed CPFs induced granularity in hPod in a dose- and time-dependent manner. Corresponding remission plasmas induced no or less granularity in hPod. Similar results were obtained with ciGEnC and mGEnC, although induced granularity was less compared with hPod. Notably, foetal calf serum, healthy plasma and a remission plasma partially blocked FSGS plasma-induced hPod granularity. Conclusions: We developed a novel assay in which active disease, presumably CPF-containing, FSGS plasmas induced granularity in cultured hPod. Our results may indicate the presence of CPF inhibitor(s) in healthy and remission plasma. We suggest the presence of a delicate balance between CPF and a CPF inhibitory factor, which is disturbed in patients with active disease. Our novel assays can be applied in future research to identify CPF and CPF inhibitors, and possibly to predict recurrence after TX.